Mapping developmental trajectories of attention and working memory in fragile X syndrome: developmental freeze or developmental change? - Cornish, K; Cole, V; Longhi, E; Karmiloff-Smith, A; Scerif, G (2013)
Fragile X syndrome (FXS) has a characteristic cognitive "signature" that by late childhood includes core weaknesses in attention and working memory (WM), but their earlier developmental trajectories remain uncharted. Using a combined cross-sectional and prospective longitudinal design, we tested whether early profiles of attention and WM impairment in FXS indicate developmental freeze or developmental change. In Study 1, 26 young boys with FXS and 55 typically developing (TD) boys completed two experimental paradigms designed to assess cognitive aspects of attention and WM, in addition to behavioral indices of inattention and hyperactivity. Study 2 mapped longitudinal changes in 21 children with FXS and 21 TD children. In Study 1, significant weaknesses emerged for boys with FXS, with no substantial improvement over chronological age. Mapping performance against mental age level revealed delay, but it also yielded a similar attention and WM profile to TD boys. In Study 2, longitudinal improvements for boys with FXS paralleled those in TD children. In conclusion, cognitive attention and WM, although delayed in FXS, reveal developmental change, rather than "arrest." Our findings underscore the need for going beyond cross-sectional group comparisons and gross behavioral indices to map cognitive changes longitudinally in developmental disorders.